In cellulo FRET-FLIM and single molecule tracking reveal the supra-molecular organization of the pyoverdine bio-synthetic enzymes in Pseudomonas aeruginosa. (2020) - Gasser, Véronique; Malrieu, Morgane; Forster, Anne; Mély, Yves; Schalk, Isabelle J.; Godet, Julien
Abstract: The bio-synthesis of pyoverdine (PVD) in Pseudomonas aeruginosa involves multiple enzymatic steps including the action of non-ribosomal peptide synthetases (NRPSs). One hallmark of NRPS is their ability to make usage of non-proteinogenic amino-acids synthesized by co-expressed accessory enzymes. It is generally proposed that different enzymes of a secondary metabolic pathway assemble into large supra-molecular complexes. However, evidence for the assembly of sequential enzymes in the cellular context is sparse. Here, we used in cellulo single-molecule tracking and Förster resonance energy transfer measured by fluorescence lifetime microscopy (FRET-FLIM) to explore the spatial partitioning of the ornithine hydroxylase PvdA and its interactions with NRPS. We found PvdA was mostly diffusing bound to large complexes in the cytoplasm with a small exchangeable trapped fraction. FRET-FLIM clearly showed that PvdA is physically interacting with PvdJ, PvdI, PvdL, and PvdD, the four NRPS involved in the PVD pathway in Pseudomonas aeruginosa PAO1. The binding modes of PvdA were strikingly different according to the NRPS it is interacting with, suggesting that PvdA binding sites have co-evolved with the enzymatic active sites of NRPS. Our data provide evidence for strongly organized multi-enzymatic complexes responsible for the bio-synthesis of PVD and illustrate how binding sites have evolved to finely control the co-localization of sequential enzymes and promote metabolic pathway efficiency.